Ratna Serumpaet Hoax and Discourse War on Social Media : Hoax Ratna Serumpaet dan Perang Wacana di Media Sosial - Rasid Pora; Dafrin Muksin; Sahrul Pora (JOURNAL OF GOVERNMENT SCIENCE, 2022)
Social media is a technology facility, which is currently widely used by the public. As is known, social media is the most frequently used tool to spread false news. This study uses a qualitative method with a descriptive approach. Data obtained through the study of Literature and reporting on several news websites. The purpose of this study was to determine how the spread of Hoax Ratna Sarumpaet and its impact socially and politically. The results of the study show that the spread of the hoax of Ratna Sarumpaet's hoax in 2018, which was spread through social media, resulted in social and political chaos. Mutual attacks between supporters and the success team of the two groups continue to occur both in social media, online and mass media.